Advancements in the Transdermal Drug Delivery Systems Utilizing Microemulsion-based Gels - Song, Yongjian; Chen, Wei; Yin, Yu; Li, Jiunian; Wang, Meng; Liu, Yi; Ren, Xiaoliang (Current Pharmaceutical Design, 2024)
Microemulsion gel, as a promising transdermal nanoparticle delivery system, addresses the limitations of microemulsions and enhances their performance in drug delivery and release. This article aims to discuss the advantages of microemulsion gel, including improved drug bioavailability, reduced drug irritation, enhanced drug penetration and skin adhesion, and increased antimicrobial properties. It explores the methods for selecting microemulsion formulations and the general processes of microemulsion preparation, as well as commonly used oil phases, surfactants, and co-surfactants. Additionally, the biomedical applications of microemulsion gel in treating conditions, such as acne and psoriasis, are also discussed. Overall, this article elucidates the significant potential of microemulsion gel in topical drug delivery, providing insights into future development and clinical applications.
Keywords: hydrogel